Implementation of Qur’anic Values in the Curriculum Management of Islamic Education - Heni Suhertini; Cecep Anwar; Linda Meliawati; Deuis Aisah (Al-Qalam Institue, 2025)
This study explores the integration of Qur'anic values into curriculum management at Madrasah Aliyah YPI Cikoneng, Bandung Regency, addressing the challenges of balancing modern educational demands with maintaining a Qur'anic identity. The study aims to examine how Qur'anic values are incorporated into curriculum planning, implementation, and evaluation. Using a qualitative descriptive approach, the research involved interviews, observations, and document analysis with key informants, including the principal, Islamic Religious Education (PAI) teachers, and students. The findings reveal that Qur'anic values are embedded in the school's vision and mission, integrated into teaching methods, and evaluated through character assessments. The study highlights the importance of aligning Leadership, teacher competence, and school culture in successfully implementing Qur'anic-based education. While the school's approach has been practical, challenges such as limited Qur'anic literacy and infrastructure remain. This research contributes to Islamic education by offering a practical model for integrating Qur'anic values into curriculum management and providing insights for other madrasahs to adopt similar approaches to maintaining spiritual and academic balance.